Criminal liability of the self-driving cars for the injury caused by it - Mohammad Reza Barzegar; Gholam Hussein Elham (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2020)
The advancement of technology has led to the production of a car that does not require a human driver. In June 2016, the first self-driving car was successfully tested in Iran and in the same month their use was banned by traffic police chief due to lack of relevant laws and lack of clear liability for possible accidents. The present study seeks to investigate how, with current criminal laws, it is possible to resolve issues arising from injuries caused by self-driving car. In this paper, regardless of other factors, only the criminal liability of the car user has been addressed. The present paper proceeds with a descriptive-analytical approach and adapts the existing rules on the self-driving car. Examining the aspects of this issue, the current study concluded that basis for imposing liability on a user at zero, one and two levels is similar to that of ordinary cars, since ultimately the user is liable for any result generated from the combination of user's driving and driver assistance systems. The basis of liability at level three is user's omission. The self-driving car at level four is a combination of level three and five of self-driving cars and regarding the user's